The ambivalence of protest in theater and music in post-1964 Brazil - Toledo, Paulo Bio (Sala Preta, 2015)
In the early years after the Brazilian military coup of 1964, theater and music experienced central dilemmas to their development. On one hand, there was the attempt to aesthetically resist the arbitrariness and the interruption of popular experiences of the previous period, on the other hand, the enthusiasm with the success of new production, and the extent of mass industry. The article discusses these issues in the text and songs of theatre play Arena conta Zumbi, from Augusto Boal and Gianfrancesco Guarnieri, as well as in Maria Bethania’s replay of Vivo num tempo de guerra, in 1965, a key song of the theater play and emblematic for the period. Finally, it analyzes Boal’s critics of the left-wing culture post-1964 in the program of I Feira Paulista de Opinião.